Pengaruh Terapi Kelompok Terapeutik Terhadap Kemampuan Keluarga dalam Memberikan Stimulasi Perkembangan Rasa Percaya Usia Bayi di Kelurahan Batu Ampar Kramatjati Jakarta Timur Tahun 2010 - Damayanti, Rika (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2014)
The aim of this research her to get comprehensive picture about the influence therapeutic group therapy to family’s ability stimulating for infant, and infant development trust in district of Batu Ampar, Kramatjati Jakarta Timur. Design research is “Quasi experimental design with pre post test approach on intervention and kontrol group." sample is purposive sampling with sample size 80 mother. Therapy group therapy conducted in the with seven sessions provide stimulation aspects of motor, cognitive, language, emotion, personality, moral, spiritual, psychosocial. Results showed increased cognitive ability, psychomotor, and infant development of trust is significantly (p-value <0.05). Increased cognitive skills, psychomotor and growth-child trust was significantly higher in mother who receive therapy compared with treatment groups that received no therapy group therapy (p-value <0.05). Therapeutic group therapy is recommended to be done within the framework of health services in the community as a form of mental health services for mother with infant age.